Electrochemical Performance of LiNixMnyCozO2 (NMC) Materials with Hollow Spheres Morphology. (18th November 2019) - Zukalova, Marketa; Prochazka, Jan; Zukal, Arnost; Kavan, Ladislav
Abstract : Electrochemical performance of the materials NMC333, NMC622 and NMC532 with hollow spheres morphology is evaluated both on a thin electrode and in a 3D arrangement in the battery module. Cyclic voltammetry of Li insertion provides charge capacities of 124, 154 and 142 mAh/g for thin electrodes containing NMC622, 532 and 333, respectively. NMC333 in the 3D battery arrangement provides 82.5% of the theoretical capacity after 5 formatting and 5 testing cycles at the C/20 and C/10 rates, respectively. NMC622 and NMC532 exhibit, under the same conditions, capacities of 64.0% and 64.6% of the theoretical battery capacity, respectively. The worse performance of the Ni-rich NMCs is ascribed to their higher reactivity with electrolyte during formatting.